Practices of teachers from preschools espousing progressive educational philosophy - Vidal, Vijaya Torres (2008)
The invencion is a ritual practice performed in honor of the Holy Cross. This paper is an ethnographic study which documents and analyzes the invencion in the social context of the town of Calabanga, Camarines Sur. The annual performance of this celebration on the third day of May is supported by an elaborate system of family sponsorship and land ownership rotated among the kindred and the heirs of its initiators, the Danabar, Reganit and Barba patriarchs. The ritual practice consists of three indispensable artistic components: the koronasyon, the lagaylay and the dalit. These three parts honor the Holy Cross through the performance of women who take the roles of Queen Elena and her attendants in elaborate song and dance sequences. The dynamics of familia (family), uma (land) and power (isog) are revealed in the discussion of the formal and cultural elements of the invencion. These elements, together with the social dynamics are examined in order to determine the significance and meaning of the devotion in Calabanga society. The invencion is important because it is regarded as lived history and experience, symbol and symbolic representation of power relationships, agricultural ritual and Panopticon. Although the interest in, appreciation of and enthusiasm for the tradition has declined in recent years, the ritual practice prevails because it is a personal devotion to the Holy Cross anchored on the familia and the uma which has supported its existence for hundreds of years and will guarantee its continuity in the future.
Thesis (M. Family Life and Child Devlopment)--University of the Philippines Diliman.
Keywords: Women Preschool teachers; Progressive education